Legal Review of SISKA KU INTIP Program as Substitution for Plasma Obligations in Livestock Partnerships - Rahman, Rojali; Munawar, Akhmad; Hidayatullah, Hidayatullah; Listiyani, Nurul; Megasari, Indah Dewi (JURNAL AKTA, 2025)
This research examines the SISKA KU INTIP Program (Palm Oil–Cattle Integration System Based on Core–Plasma Livestock Business Partnerships) as a role model for partnerships between palm oil plantation companies and communities. This program is an alternative to the obligation to build plasma plantations of 20% of the area regulated in Law No. 39 of 2014 concerning Plantations. In practice, limited land and high levels of agrarian conflict often hinder the implementation of plasma. SISKA KU INTIP offers a more flexible and productive solution through a palm-cattle integration. This research aims to: (1) find out how the SISKA KU INTIP program is implemented in oil palm plantations, and (2) analyze the legal politics in supporting this program as a role model for developing cattle-oil palm integration as a substitute for plasma obligations in Indonesia. The research method was normative juridical, with a statutory regulation and legal policy approach. Data was obtained through a literature study of primary, secondary, and tertiary legal materials. The analysis is carried out systematically, teleologically, in legal politics, legal discovery (reasoning and interpretation), and legal certainty. The research results show that although it has not been explicitly regulated as a substitute for plasma obligations, SISKA KU INTIP has a legal basis in various supporting sectoral and regional regulations. In addition, several academic studies have been conducted regarding the results or impact of SISKA KU INTIP on the plantation sector. This program can be applied normatively, technically, and socially as a model for substituting plasma obligations, as long as there is policy harmonization between the central and regional governments. This program also supports social justice and sustainable development through the values of Pancasila and the 1945 Constitution.